2015
DOI: 10.1124/dmd.115.066852
|View full text |Cite
|
Sign up to set email alerts
|

Cynomolgus Monkey as a Clinically Relevant Model to Study Transport Involving Renal Organic Cation Transporters: In Vitro and In Vivo Evaluation

Abstract: Organic cation transporter (OCT) 2, multidrug and toxin extrusion protein (MATE) 1, and MATE2K mediate the renal secretion of various cationic drugs and can serve as the loci of drug-drug interactions (DDI). To support the evaluation of cynomolgus monkey as a surrogate model for studying human organic cation transporters, monkey genes were cloned and shown to have a high degree of amino acid sequence identity versus their human counterparts (93.7, 94.7, and 95.4% for OCT2, MATE1, and MATE2K, respectively). Su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 50 publications
2
40
1
Order By: Relevance
“…Determined IC 50 (K i ) values (Table 2) versus OCT2, MATE1 and MATE2-K were in reasonable concordance with literature values and were much lower (35-to 170-fold; Fig. 1) for MATEs versus OCT2 (Kusuhara et al 2011;Ito et al 2012;M€ uller et al 2015;Shen et al, 2016). However, only inhibition constants for OCT2 and MATE1 were subsequently incorporated into mechanistic equations for predicting metformin AUC increases as the study of Prasad et al (2016) determined that these, and not MATE2-K, are the major cationic transporter proteins expressed in human renal proximal tubules; representing 26% and 18% of renal transporter protein.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Determined IC 50 (K i ) values (Table 2) versus OCT2, MATE1 and MATE2-K were in reasonable concordance with literature values and were much lower (35-to 170-fold; Fig. 1) for MATEs versus OCT2 (Kusuhara et al 2011;Ito et al 2012;M€ uller et al 2015;Shen et al, 2016). However, only inhibition constants for OCT2 and MATE1 were subsequently incorporated into mechanistic equations for predicting metformin AUC increases as the study of Prasad et al (2016) determined that these, and not MATE2-K, are the major cationic transporter proteins expressed in human renal proximal tubules; representing 26% and 18% of renal transporter protein.…”
Section: Discussionsupporting
confidence: 85%
“…; Müller et al. ; Shen et al., ). However, only inhibition constants for OCT2 and MATE1 were subsequently incorporated into mechanistic equations for predicting metformin AUC increases as the study of Prasad et al.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that CPs could be potential endogenous biomarkers of OATP activity in vivo (Benz-de Bretagne et al, 2011;van de Steeg et al, 2012). Indeed, the plasma concentrations of both CP-I and CP-III in cynomolgus monkeys were markedly increased following administration of OATP inhibitors cyclosporine A (100 mg/kg oral) or RIF (15 mg/kg oral) (Shen et al, 2015(Shen et al, , 2016b. The observations in monkey could explain the clinical findings that cyclosporine A-or RIF-induced porphyria in patients is likely due to the inhibition of OATP transporters (Millar, 1980;Hivnor et al, 2003).…”
Section: Discussionmentioning
confidence: 89%
“…In this work we chose a human embryonic kidney cell‐line 293 T (HEK‐293 T) to evaluate the effects on DNA damage of the latest described potential biomarker for FD – lyso‐Gb3 – regarding to oxidative damage. HEK‐293 and HEK‐293 T cells have been used as a model of epithelial kidney cell‐line in renal physiology studies . To reproduce pathological conditions, all experiments were done using lyso‐Gb3 in concentrations found in plasma of Fabry patients: 10, 50 and 100 nM .…”
Section: Discussionmentioning
confidence: 99%
“…HEK-293 and HEK-293 T cells have been used as a model of epithelial kidney cell-line in renal physiology studies. [14][15][16][17] To reproduce pathological conditions, all experiments were done using lyso-Gb3 in concentrations found in plasma of Fabry patients: 10, 50 and 100 nM. 5,[7][8][9][10] To the best of our knowledge, this is the first study focusing on these effects of lyso-Gb3.…”
Section: Discussionmentioning
confidence: 99%